Morphometric analysis of forewing venation does not consistently differentiate the leafhopper tribes Typhlocybini and Zyginellini - Wen, Hui; Zhou, Xian; Dietrich, Christopher H.; Huang, Min (Frontiers in Ecology and Evolution, 2022)
Tribes of the leafhopper subfamily Typhlocybinae have traditionally been defined based on differences in hind wing venation, but the forewing venation also differs among some tribes. Here we used geometric morphometric analysis to determine whether previously recognized tribes can be distinguished based on the configuration of forewing veins. Focusing on the apical area of the male right forewing, 76 semi-landmarks in 6 curves corresponding to individual wing veins were measured for representatives of four previously recognized tribes and the data were analyzed using principal component analysis (PCA), canonical variable analysis (CVA) and UPGMA clustering analysis. The study showed that differences in the apical area of the forewing mainly occur in RP, MP' and MP''+CuA'. PCA, CVA and cluster analysis showed three distinct clusters representing tribes Empoascini, Erythroneurini and Typhlocybini (sensu lato) but failed to distinguish Typhlocybini (sensu stricto) from Zyginellini, which has been considered as either separate tribe or a synonym of Typhlocybini by recent authors. The results show that the forewing venation differs among tribes of Typhlocybinae, but also agree with recent molecular phylogenetic analyses, indicating that Zyginellini is derived from within Typhlocybini.